Peningkatan Kreativitas Menulis dan Motivasi Belajar Bahasa Inggris Kelas II Melalui Penerapan Metode Storytelling Pada Siswa di SDS XYZ Jakarta - Gadiza Olivia (Jurnal Ketopong Pendidikan, 2024)
Writing a good short story needs a creativity. However, the researcher is concerned about the level of students’ creativity in writing and the learning motivation that needs improvement. This triggers the researcher to conduct a research in the class or Classroom Action Research (CAR) through the implementation of storytelling method. The aims of this research are (1) Describing the implementation of storytelling that improves creativity in writing and the motivation to learn English. (2) Analyzing the development of students’ creativity after applying storytelling method. (3) Analyzing the development of students’ learning motivation after applying storytelling method. (4) Describing the obstacles that occur during the application of the storytelling method. This research is conducted in three cycles. The subject of this research is 16 students of grade II. Data were collected through observation, notes, interview, and writing tests with three different instruments. Then the data were being analyzed in descriptive qualitative. The results showed that (1) all activities and corrective actions are carried out in accordance with the storytelling lesson plan (2) there was a development of creativity in writing up to 80% (3) there was a development of learning motivation up to 89%, and (4) the obstacles are the difficulties in developing ideas and limited vocabularies.